Comparison of MRI Findings among Osteofibrous Dysplasia, Fibrous Dysplasia, and NonOssifying Fibroma of the Long Bone - Kato, Hiroki; Kawaguchi, Masaya; Miyase, Rena; Iwashima, Ken; Nagano, Akihito; Matsuo, Masayuki (Indian Journal of Radiology and Imaging, 2023)
Background The characteristics of magnetic resonance imaging (MRI) findings among osteofibrous dysplasia (OFD), fibrous dysplasia (FD), and nonossifying fibroma (NOF) have yet to be determined.Aims This study determines the differences of MRI features among OFD, FD, and NOF of the long bone.Patients and Methods This study included 39 patients including 10 OFD, 13 with FD, and 16 with NOF of the long bone. All patients underwent preoperative MRI and histological examination. We retrospectively reviewed the MRIs and compared the imaging findings among the three pathologies.Results The maximum diameter was significantly different among OFD (47.0 ± 18.6 mm), FD (59.0 ± 35.0 mm), and NOF (33.3 ± 15.0 mm) (p < 0.05). Multiplicity (60%, p < 0.01), eccentric distribution (100%, p < 0.05), septation (70%, p < 0.01), homogeneous intensity on T2-weighted images (70%, p < 0.01), homogeneous contrast enhancement (63%, p < 0.05), and intense contrast enhancement (88%, p < 0.01) were significantly more frequent in OFD. Centric distribution (69%, p < 0.01), cyst formation (54%, p < 0.01), and fluid-fluid level formation (31%, p < 0.01) were significantly more frequent in FD. Eccentric distribution (100%, p < 0.01), heterogeneous on T2-weighted images (100%, p < 0.01), predominant hypointensity on T2-weighted images (44%, p < 0.01), and the presence of intralesional hypointensity on T2-weighted images (88%, p < 0.01) were significantly more frequent in NOF.Conclusion MRI features could differentiate OFD, FD, and NOF of the long bone.
Keywords: MRI; osteofibrous dysplasia; fibrous dysplasia; nonossifying fibroma